Addicted to Rehab : Race, Gender, and Drugs in the Era of Mass Incarceration - Jackson, Lawrence Patrick (Book collections on Project MUSE., 2022)
"The author examines actor Clint Eastwood's influence on the Western film as a genre, as well as how that genre continues to operate into the twenty-first century as an ideological channel for ideas about race and imperialism"--